Intercultural Competence: a scaffold for professional excellence - Pierre Murray, Kattia (2021)
The 21st century requires professionals with intercultural skills that can perform efficiently and effectively, in an increasingly interconnected and globalize environment, in which information and communication technologies has a central role. Internationalization has been one of the strategies most used by Higher Education institutions, around the world, with the purpose of promoting the development of intercultural competences in students and teachers. In the current context, it is necessary to examine the concepts of multiculturalism, interculturality and culture and the way they are reflected in the policies and curriculum of the University of Costa Rica. This study analyzes some actions and policies implemented at the University of Costa Rica that aim to promote academic excellence through internationalization. However, these competencies are tacitly integrated in the curriculum of the University of Costa Rica.